2021
DOI: 10.1029/2021gl094978
|View full text |Cite
|
Sign up to set email alerts
|

Data‐Driven Identification of Turbulent Oceanic Mixing From Observational Microstructure Data

Abstract: Turbulence significantly enhances the vertical transport of heat and other scalars throughout the ocean, playing a vital role in maintaining ocean stratification and driving global currents such as the meridional overturning circulation (Wunsch & Ferrari, 2004). Despite having a leading order effect on ocean dynamics and climate modeling, turbulent processes cannot currently be resolved in ocean circulation models and must therefore be parameterized, typically in terms of an eddy diffusivity (Fox-Kemper et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 40 publications
6
19
0
Order By: Relevance
“…In agreement with the analysis of oceanographic data by Couchman et al. (2021), figure 2( d ) demonstrates that although the majority of the domain indeed appears to be well characterized by the canonical flux coefficient , significantly elevated is associated with the most extreme events in , events that are not reflected by a corresponding local increase in . Given the current relative sparsity of measurements within the ocean, mixing parametrizations may thus be biased towards the most commonly measured events, which are not necessarily the most significant.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In agreement with the analysis of oceanographic data by Couchman et al. (2021), figure 2( d ) demonstrates that although the majority of the domain indeed appears to be well characterized by the canonical flux coefficient , significantly elevated is associated with the most extreme events in , events that are not reflected by a corresponding local increase in . Given the current relative sparsity of measurements within the ocean, mixing parametrizations may thus be biased towards the most commonly measured events, which are not necessarily the most significant.…”
Section: Discussionsupporting
confidence: 90%
“…Comparing the right panels of figures 2( e ) and 2( f ) reveals that is far more dominated by extreme events than , in agreement with the analysis of oceanographic data by Couchman et al. (2021). For instance, when each tail contains volume, the stable (blue) and unstable (red) tails each contain approximately of the total in the domain, but and of the total , respectively.…”
Section: Pointwise Statistics Conditioned On Local Density Gradientsupporting
confidence: 87%
See 1 more Smart Citation
“…A cutoff of T z > 1 × 10 −4 °C m −1 was used in the calculation of ϵ χ (Alford & Pinkel, 2000). While ϵ and ϵ χ may differ due to both physical or sampling-related reasons (Couchman et al, 2021;Gregg et al, 2018;Taylor et al, 2019) agreement between ϵ and ϵ χ computed from MMP data (not shown) was generally within a factor of two.…”
Section: Fastctdmentioning
confidence: 98%
“…The wealth of data available from DNS may be readily utilised by machine learning methods, which have become a popular choice for reduced order modelling of fluid flows due to their inherent ability to capture complex spatio-temporal dynamics [2,12,14] and reveal insights into flow physics [5,3]. Recently, practical uncertainty estimates available from probabilistic neural networks have been gaining increasing popularity in geophysical and environmental applications [9,1].…”
Section: Introductionmentioning
confidence: 99%